CLIMATE CHANGE INFORMATION NEEDS OF RURAL FARMERS IN ENUGU STATE - John Chukwuma Okoro; Agwu Ekwe Agwu; Ifeoma Quinette Anugwa (Journal of Agricultural Extension, 2016)
The study assessed the information needs of rural farmers on climate change issues in Enugu State, Nigeria. Using the multistage sampling procedure, 152 respondents were selected and data were collected through the use of a structured interview schedule. Descriptive statistics, factor analysis and multiple linear regression model were used for the analysis. Results of the study show that all (100.0%) the respondents were aware of climate change, but lacked adequate knowledge of key climate change issues. The multiple linear regression model revealed a significant influence of years of formal education (t= 2.020; p=0.045), membership of social organizations (t=2.385; p=0.019) number of climate change training (t= -2.438; p=0.016), farm size (t=2.564; p=0.011), and access to credit (t=2.833; p=0.005) on the respondentsâ€™ level of knowledge on climate change. The information needs on climate change as perceived by farmers were: use of improved varieties (M=1.80), occupational diversification (M=1.78), and change in timing of farm operations (M=1.76), among others. The study therefore recommends that farmers should be taught climate change adaptation and mitigation measures using languages they can understand and in a participatory manner so as to enable them cope with the challenges of climate change.Â